Branding Desa Sambimulyo sebagai Destinasi Wisata Kebun Jeruk - Seno, Intan Aprilia; Sayekti, Pranti; Arizal, Fariza Wahyu (Indonesian Journal for Social Responsibility, 2025)
Sambimulyo Village is a village in Bangorejo Sub-district, Banyuwangi Regency that has the potential of citrus fruit farming which requires a branding program to form its identity as a tourist destination. This branding program is carried out by forming a visual identity, developing tourism activities, developing typical products, developing areas, and empowering human resources to regulate tourism regulations. The design of the branding program was carried out using a qualitative method with the 2013 Alina Wheeler model starting from determining the topic, researching problems, clarifying strategies through observation, interviews, questionnaires, and documentation. The results of this branding program design are implemented in identity design in the form of a logo, and GSM (Graphic Standard Manual) which is applied to promotional media in the form of banners, billboards, brochures, social media content, and websites. Development of tourist areas and activities supported by making signage designs, backdrops, regular tickets, festival tickets, and festival posters. Making typical products supported by menu book design, product packaging, merchandise. And empowering the surrounding community by socializing the branding program, providing training, and coordinating to manage tourism.